IRISS '98: The Intranet as a Learning Tool: A Preliminary Study - K. J. Garland; S. J. Anderson; J. M. Noyes (Information Research: An International Electronic Journal)
Using the World Wide Web (WWW) as an interactive educative tool is still a relatively new concept, and little is known of its impact on learning when it is used as a dynamic learning tool. Despite this the use of educational internet sites, in the form of virtual classrooms and courses, appears to be increasing rapidly. Thus, it is important that their ability to facilitate learning is evaluated. We present the findings of a preliminary study which examined the amount, type and quality of leaning of an undergraduate indroductory history course when presented to three different groups of participants. All participants received four regularly spaced 30 minute study and repeated test sessions over an eight day period. A final test of new questions was also administered at the end of the study. Results showed that the amount of historical knowledge acquired by the end of the study was greatest for those paticpants who learnt using traditional methods, and that over the four test sessions this group consistently outperformed both computer groups. Moreover, the way in which knowledge was acquired was qualitatively different in the groups with the traditional group exhibiting more 'Know' responses while the Intranet group exhibited more 'Remember' responses. Finally, using useability questionnaires, we found that participants preferred learning via traditional methods to screen and Intranet presentations, and that participants who had learnt using computers felt that their learning experience had suffered. These findings have important implications for educators, and others who wish to use the Internet as a training tool, and we discuss our findings through the evaluation of the different presentational media used, specific Intranet design criteria and general usability factors, which, we suggest, are of paramount importance.